2019
DOI: 10.1017/s1431927619014776
|View full text |Cite
|
Sign up to set email alerts
|

Functional Validation of DownRegulated MicroRNAs in HeLa Cells Treated with Polyalthia longifolia Leaf Extract Using Different Microscopic Approaches: A Morphological Alteration-Based Validation

Abstract: Several microscopy methods have been developed to assess the morphological changes in cells in the investigations of the mode of cell death in response to a stimulus. Our recent finding on the treatment of the IC50 concentration (26.67 μg/mL) of Polyalthia longifolia leaf extract indicated the induction of apoptotic cell death via the regulation of miRNA in HeLa cells. Hence, the current study was conducted to validate the function of these downregulated microRNAs in P. longifolia-treated HeLa cells using micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Beside the inactivation of those proliferative and pro-inflammatory signaling cascades, Shanmugapriya et al (2019 and 2020) reported that polyphenol-rich P. longifolia extracts induced HeLa cell apoptosis by down-regulation of oncogenic micro-ribonucleic acid (miRNA)-221-5p in HeLa cells [107,108]. MicroRNA is a non-coding small RNA, which consists of about 21-25 nucleotides in length and is base-pairing to the targeted messenger RNA (mRNA) [109].…”
Section: Cytotoxic/anti-tumor Phytochemicals In Polyalthia and The Molecular Mechanism Of Cd-induced Tumor Cell Deathmentioning
confidence: 99%
“…Beside the inactivation of those proliferative and pro-inflammatory signaling cascades, Shanmugapriya et al (2019 and 2020) reported that polyphenol-rich P. longifolia extracts induced HeLa cell apoptosis by down-regulation of oncogenic micro-ribonucleic acid (miRNA)-221-5p in HeLa cells [107,108]. MicroRNA is a non-coding small RNA, which consists of about 21-25 nucleotides in length and is base-pairing to the targeted messenger RNA (mRNA) [109].…”
Section: Cytotoxic/anti-tumor Phytochemicals In Polyalthia and The Molecular Mechanism Of Cd-induced Tumor Cell Deathmentioning
confidence: 99%
“…Figure shows a fluorescence amplitude image recorded at the emission wavelength of the calcein dye (green), merged with the corresponding ACS amplitude magnetic image from the same region (false color, red). Many live cells can be seen in this low magnification image, displaying a typical morphology for this cell line (see, e.g., Shanmugapriya et al). Where S1 MNPs are colocalized with live cells, they appear orange/yellow in the image (due to the overlapping color channels), whereas MNPs that have deposited onto the bottom of the cell culture holder appear red.…”
Section: Resultsmentioning
confidence: 99%
“…When AW1 cells were treated with 60 μM NCB for 24 h, typical apoptotic characteristics such as nuclear condensation and swollen mitochondria were observed (Ren et al, 2021a). When AW1 cells were treated with 80 and 100 μM NCB for 24 h, the TEM images showed apparent mitochondrial swelling (X. Wang et al, 2015) and cell shrinkage and convolution (Shanmugapriya & Sasidharan, 2019). Moreover, organelle vacuolation and apoptotic bodies were observed (L. Yang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…When AW1 cells were treated with 80 and 100 μM NCB for 24 h, the TEM images showed apparent mitochondrial swelling (X. Wang et al, 2015) and cell shrinkage and convolution (Shanmugapriya & Sasidharan, 2019). Moreover, organelle vacuolation and apoptotic bodies were observed (L. Yang et al, 2016).…”
Section: Effect Of Ncb On Morphological Changes In Aw1 Cellsmentioning
confidence: 99%